1999
DOI: 10.1117/12.364402
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced blood serum fluorescence and Raman spectroscopy for cancer diagnosis

Abstract: laser induced auto-fluorescence and Raman spectra of serum from cancerous and normal people are measured and analyzed .The content of -carotene ( f3 -BC)m the serum from normal man is higher than that from the cancerous one ,this result agrees with other reports. INTREDUCTIONLaser induced fluorescence spectroscopy and Raman spectroscopy are two kinds of optical tools to be used to probe the molecular structure and contents .It is well known that big biological molecules chromophores such as protein , flavins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
1
2
0
Order By: Relevance
“…The authors achieved a 90% sensitivity utilizing LDA of the PCA scores and concluded that differences in Raman spectra were related to beta-carotene levels (peaks around 1155 and 1523); with generally lower values in the cancer cohort. Similar findings were reported by Li et al .2001 using a Raman system with incident wavelengths of 488 nm and 514.5 nm [ 17 ]. A large training set of 1022 samples containing various malignancies, healthy controls and other diseases was used, followed by 432 test samples.…”
Section: Discussionsupporting
confidence: 90%
“…The authors achieved a 90% sensitivity utilizing LDA of the PCA scores and concluded that differences in Raman spectra were related to beta-carotene levels (peaks around 1155 and 1523); with generally lower values in the cancer cohort. Similar findings were reported by Li et al .2001 using a Raman system with incident wavelengths of 488 nm and 514.5 nm [ 17 ]. A large training set of 1022 samples containing various malignancies, healthy controls and other diseases was used, followed by 432 test samples.…”
Section: Discussionsupporting
confidence: 90%
“…Several reports already indicate the utility of spectroscopic signatures of blood for several diseases, including cancers [15][16][17][18][19][20][21] . Raman spectroscopy for detection of cancers like breast, cervix, nasopharynx, colorectal, gastric and head and neck has already been explored [22][23][24][25][26] . A previous study for detection of oral cancers has indicated a classification efficiency of ~ 70% for oral cancers and normal subjects using a commercial Raman microscope fitted with a green laser (532 nm) 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Several IR spectroscopy studies on blood have shown its potential in detecting various diseases including Alzheimer’s, scrapie, sickle cell anaemia and several cancers [ 20 - 25 ]. Raman spectroscopy (RS), a vibrational spectroscopic method based on inelastic scattering of light, has been widely used for qualitative characterization of biological tissues [ 26 - 28 ], for diagnosis of periodontitis and lung cancer from saliva [ 29 , 30 ], breast cancers [ 31 ], atherosclerosis [ 32 ] and also for several cancers using serum [ 33 - 36 ]. For quantitative analysis, RS has been employed for determining glucose and other analytes in blood [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%